PENGARUH LINGKUNGAN KERJA NON FISIK, DISIPLIN KERJA DAN PENGEMBANGAN KARIR TERHADAP KINERJA PERSONIL ANGGOTA SEKOLAH POLISI NEGARA (SPN) POLDA SULTRA - Muh. Yusran; Ibnu Hajar; Juharsah Juharsah (Pascasarjana Universitas Halu Oleo, 2023)
The purpose of this study was to examine and explain the effect of non-physical work environment, work discipline and career development on the performance of the National Police School (SPN) members of the Southeast Sulawesi Regional Police either simultaneously or partially. The approach of this study is quantitative using a survey method. The data was collected by cross section using a one-line questionnaire with the link: https://forms.gle/H515BEQpSkcQZpU59. The sample of this study was all 68 members of the SPN Polda Sultra police. The analytical tool used is Multivariate Regression AnalysisThe results of this study indicate that the non-physical work environment, work discipline and career development together have a positive and significant effect on police performance. The results of the partial test of the non-physical work environment proved to have a positive and significant effect on the performance of the police. Then work motivation has a positive and significant effect on police performance. These results prove that the better the career development, the significantly the police performance will increase. This result is also strengthened by the respondent's statement based on the respondent's description non-physical work environment, work discipline, career development and police performance, the majority of respondents stated that the implementation was good at the SPN Polda Sultra.